Mu opioid receptor stimulation in the medial preoptic area or nucleus accumbens facilitates song and reward in flocking European starlings - Polzin, Brandon J.; Maksimoski, Alyse N.; Stevenson, Sharon A.; Zhao, Changjiu; Riters, Lauren V. (Frontiers in Physiology, 2022)
It has been proposed that social cohesion in gregarious animals is reinforced both by a positive affective state induced by social interactions and by the prevention of a negative state that would be caused by social separation. Opioids that bind to mu opioid receptors (MORs) act in numerous brain regions to induce positive and to reduce negative affective states. Here we explored a potential role for MORs in affective states that may impact flocking behavior in mixed-sex flocks of nonbreeding European starlings, Sturnus vulgaris. Singing behavior, which is considered central to flock cohesion, and other social behaviors were quantified after infusions of the MOR agonist D-Ala2, N-Me-Phe4, glycinol5-ENK (DAMGO) into either the medial preoptic area (POM) or the nucleus accumbens (NAC), regions previously implicated in affective state and flock cohesion. We focused on beak wiping, a potential sign of stress or redirected aggression in this species, to provide insight into a presumed negative state. We also used conditioned place preference (CPP) tests to provide insight into the extent to which infusions of DAMGO into POM or NAC that stimulated song might be rewarding. We found that MOR stimulation in either POM or NAC dose-dependently promoted singing behavior, reduced beak wiping, and induced a CPP. Subtle differences in responses to MOR stimulation between NAC and POM also suggest potential functional differences in the roles of these two regions. Finally, because the location of NAC has only recently been identified in songbirds, we additionally performed a tract tracing study that confirmed the presence of dopaminergic projections from the ventral tegmental area to NAC, suggesting homology with mammalian NAC. These findings support the possibility that MORs in POM and NAC play a dual role in reinforcing social cohesion in flocks by facilitating positive and reducing negative affective states.